2014
DOI: 10.1002/ejhf.116
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs for predicting and monitoring response to mechanical circulatory support from a left ventricular assist device

Abstract: AimsThere are few non-invasive techniques to predict and monitor patients' responses to left ventricular assist device (LVAD) therapy. MicroRNAs (miRs) are small non-coding RNAs with intricate roles in cardiovascular disease. They are stable in the circulation, readily quantified, and may be useful as new biomarkers. This study sought to identify candidate miR biomarkers for further investigation.Methods and resultsWe studied 53 plasma and 20 myocardial samples from 19 patients who underwent HeartMate II LVAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…For example, miR-483-5p has been reported to control angiogenesis in vitro by targeting the transcription factor SRF1 and it is a potential therapeutic target for improving neovascularization in ischemic heart disease [14]. Abue et al proposed that miR-483-3p in blood could be a potential biomarker that can be used to predict the heart function after getting a left ventricular assist device [25]. However, there was no specific evidence to demonstrate the function of miR-483-3p in regulating cardiomyocyte apoptosis in diabetic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, miR-483-5p has been reported to control angiogenesis in vitro by targeting the transcription factor SRF1 and it is a potential therapeutic target for improving neovascularization in ischemic heart disease [14]. Abue et al proposed that miR-483-3p in blood could be a potential biomarker that can be used to predict the heart function after getting a left ventricular assist device [25]. However, there was no specific evidence to demonstrate the function of miR-483-3p in regulating cardiomyocyte apoptosis in diabetic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In vascular smooth muscles, abundantly found in blood vessels, angiotensin II-regulated miR-483-3p negatively affects homeostasis between the components of the renin-angiotensin system [24]. It has also been suggested that circulating miR-483-3p can serve as a potential biomarker in predicting and monitoring patient response to left ventricular assist device therapy [25]. However, there are no reports describing the function of miR-483-3p in diabetes-associated heart disease.…”
Section: Introductionmentioning
confidence: 98%
“…Recent work by Morley-Smith et al . [26] has demonstrated an acute and sustained increase in circulating mir-483-3p (which originates from the opposite arm of the same pre-miRNA as miR-483-5p) in heart failure patients after left ventricular assist device insertion, mirroring suppression of NT-pro-BNP secretion. Alongside our results, these findings may suggest that transcription of serum pre-miRNA-483 may be stimulated in states of cardiac stress, the mature products of which may then be detected in the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Marques et al have measured microRNAs in arterial and coronary sinus venous samples in healthy volunteers and HF patients . Upregulation or downregulation of different microRNAs and cardiac release of micro‐RNAs was found in the failing hearts, compared with controls, confirming the potential role of microRNAs as biomarkers and/or targets of treatment …”
Section: Pathophysiologymentioning
confidence: 95%